Salivary biomarkers for the diagnosis of gastric cancer: a systematic review - Zúñiga-Pérez, Natalia (2024)
Background: Recent advancements reveal saliva as a crucial source of diagnostic biomarkers for various diseases, notably gastric cancer. This systematic review evaluates these biomarkers, emphasizing their clinical applicability and potential in early detection. Methods: An extensive electronic search was conducted across PubMed/MEDLINE, Scopus, and Web of Science to identify relevant studies. Salivary biomarkers were analyzed as independent variables, with gastric cancer as the dependent variable. The study adhered to a protocol registered with PROSPERO (CRD42021259519). Results: Our analysis identified a range of biomarkers, highlighting three proteins - cystatin-B (CSTB), triosephosphate isomerase (TPI1), and deleted in malignant brain tumors 1 protein (DMBT1) - as particularly accurate for gastric cancer diagnosis. Conclusions: Salivary biomarkers hold substantial promise for the early detection of gastric cancer. Future research should aim to refine study design and validation for enhancing the quality and applicability of these biomarkers.